Referral of patients to plastic surgeons following self-harm: Opportunities for suicide prevention. Issue 3 (March 2019) - Concannon, E.; Carr, S.; Doherty, A.; McInerney, S.J.; Birrane, J.; Kearney, L.; Hussey, A.J.; Potter, S.M.; Kelly, J.L.; McInerney, N.M.
Summary: Self-harm is a common source of referral to plastic and hand surgery services. Appropriate management of these patients is complex and includes the need for close liaison with mental health services. Self-harm is the single biggest risk factor for completed suicide, thereby increasing the risk by a factor of 66. 1 This study aimed to analyse the clinical pathway and demographics of patients referred to plastic surgeons following self-harm. This 6-year retrospective series included patients referred to plastic surgeons following self-harm within the Galway University Hospital group. Patients were identified through the Hospital inpatient enquiry system, cross-referenced with data from the National Suicide Research Foundation. Data collected included demographics, psychiatric history, details of self-harm injury, admission pathway and operative intervention. Forty-nine patients were referred to plastic surgery services during the study period, accounting for 61 individual presentations. The male-to-female ratio was 26 (53%) to 23 (47%). Mean age was 40 years (range 21–95 years). Alcohol or illicit substance use was recorded in 17 of 61 (28%) presentations. Mortality from suicide occurred in 4 patients (8%). Mental health assessment was not carried out in 9 presentations (15%). Documentation of need for close or one-to-one observation was made in 11 cases (20%) and was not referred to in 43 cases (83%) following mental health assessment. This study demonstrates significant diversity in the management of this vulnerable patient group and may inform development of referral pathways to improve the safety of transfer, surgical admission and discharge of patients following self-harm, in consultation with mental health services.